2018
DOI: 10.1038/s41467-018-05992-x
|View full text |Cite
|
Sign up to set email alerts
|

EMT- and stroma-related gene expression and resistance to PD-1 blockade in urothelial cancer

Abstract: Cancers infiltrated with T-cells are associated with a higher likelihood of response to PD-1/PD-L1 blockade. Counterintuitively, a correlation between epithelial–mesenchymal transition (EMT)-related gene expression and T-cell infiltration has been observed across tumor types. Here we demonstrate, using The Cancer Genome Atlas (TCGA) urothelial cancer dataset, that although a gene expression-based measure of infiltrating T-cell abundance and EMT-related gene expression are positively correlated, these signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
205
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(225 citation statements)
references
References 50 publications
17
205
1
2
Order By: Relevance
“…More recently, Moriggi et al reported that fibrinogen, encoded by FGB, is involved in ECM remodeling, including the epithelial-mesenchymal transition (EMT) [44]. Matthew D. Galsky further confirmed that EMT-related gene expression and T-cell infiltration are positively correlated, and the balance of T-cell vs. EMT/stromal elements may have prognostic/predictive implications with the antitumor immune response [45].…”
Section: Discussionmentioning
confidence: 95%
“…More recently, Moriggi et al reported that fibrinogen, encoded by FGB, is involved in ECM remodeling, including the epithelial-mesenchymal transition (EMT) [44]. Matthew D. Galsky further confirmed that EMT-related gene expression and T-cell infiltration are positively correlated, and the balance of T-cell vs. EMT/stromal elements may have prognostic/predictive implications with the antitumor immune response [45].…”
Section: Discussionmentioning
confidence: 95%
“…Tumor metastasis begins with epithelial-mesenchymal transition (EMT), in which epithelial cells acquire a mesenchymal phenotype and become migratory and invasive (Shen et al, 2017;Wang et al, 2018). Loss of the epithelial marker E-cadherin and an increase in the expression of mesenchymal markers are characteristics of EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a subset of BATF3 + IRF8 + cDC1s are not only required for T cell trafficking, but are also necessary for the generation of effector T cell responses to anti-PD-1 therapy (17,135). Importantly, processes of metastasis co-opted by tumors such as EMT also influence DC maturation, migration, and phenotype, and are associated with ICB resistance in both melanoma and bladder cancer (136,137). These studies highlight the importance of DCs in ICB and suggest that targeting DCs to reverse tolerogenesis may sensitize previously unresponsive patients to ICB.…”
Section: Tolerization and Checkpoint Inhibitor Immunotherapymentioning
confidence: 99%